If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -12 = 3x + -2 Reorder the terms: -12 + 4x = 3x + -2 Reorder the terms: -12 + 4x = -2 + 3x Solving -12 + 4x = -2 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -12 + 4x + -3x = -2 + 3x + -3x Combine like terms: 4x + -3x = 1x -12 + 1x = -2 + 3x + -3x Combine like terms: 3x + -3x = 0 -12 + 1x = -2 + 0 -12 + 1x = -2 Add '12' to each side of the equation. -12 + 12 + 1x = -2 + 12 Combine like terms: -12 + 12 = 0 0 + 1x = -2 + 12 1x = -2 + 12 Combine like terms: -2 + 12 = 10 1x = 10 Divide each side by '1'. x = 10 Simplifying x = 10
| 4t^2-7t+2=0 | | 42-4x=14x+18 | | x(7x-8)-15=0 | | 70-6x=6+2x | | 49x+20y=28 | | (x+2)(x+2)-9x=0 | | 2(t+5)13= | | X+(x+23)=150 | | 61-5x=8+22 | | -21+21+5= | | -5(-3x+4)=16-3x | | 16+72-16= | | 44-6x=3x+24 | | 92-12+12= | | x+4=3x+16 | | 9x-50=4x+10 | | 136-6x=21x+19 | | 2x+17=11x-10 | | X^3+24X-50=0 | | 16m-9n-9m+12n-12= | | 12x+7=23+4x | | 9x-4=20+3x | | (x-.5)(x+.8)=0 | | 4x-12=x+18 | | (3x+7)(5x-7)=0 | | x^2=x^4 | | x^2-96x-636=0 | | 3x-12=x+18 | | M+n-2+2m-5n= | | 4x+3=-7(x+9) | | 1-x=5x+1 | | 6x-89=3x-8 |